Analisis Proses Rekrutmen Calon Anggota Panitia Pengawas Pemilu Kecamatan (Panwaslu Kecamatan) di Kabupaten Hulu Sungai Selatan Tahun 2022 - Yamani, Akhmad Zaki (LITERATUS, 2023)
This research explores the recruitment process for prospective members of the Subdistrict Election Supervisory Committee (Panwaslu Kecamatan) in Hulu Sungai Selatan Regency in 2022. The main focus of the research is on the selection of members of the Subdistrict Panwaslu, which includes the announcement of registration, receipt of registration forms and documents, administrative assessment, announcement of evaluation results, collecting public responses, selection through written exams with CAT Socrative, interviews, and determining the selected candidates. This research also identified various obstacles faced during the recruitment process, including delays in the disbursement of budgets from the APBN, limited facilities and infrastructure, and an uneven distribution of registration announcement information. In facing this challenge, research suggests increasing socialization of the recruitment process, the use of electronic media to receive public input, and the timely allocation of funds. The results of this research are important to ensure that the Subdistrict Panwaslu recruitment process in Hulu Sungai Selatan Regency can run more effectively and efficiently, support integrity and fairness in elections, and strengthen community participation in the democratic process.